2019
DOI: 10.1093/nar/gkz1160
|View full text |Cite
|
Sign up to set email alerts
|

Effector gene silencing mediated by histone methylation underpins host adaptation in an oomycete plant pathogen

Abstract: The relentless adaptability of pathogen populations is a major obstacle to effective disease control measures. Increasing evidence suggests that gene transcriptional polymorphisms are a strategy deployed by pathogens to evade host immunity. However, the underlying mechanisms of transcriptional plasticity remain largely elusive. Here we found that the soybean root rot pathogen Phytophthora sojae evades the soybean Resistance gene Rps1b through transcriptional polymorphisms in the effector gene Avr1b that occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 54 publications
1
53
0
Order By: Relevance
“…Tight regulation of these avirulence effectors could limit the negative effects of the host immune responses, which may be especially relevant for avirulence factors such as Avr3D1 that induce only partial resistance (51). The location of effector genes in heterochromatic regions might also make them more prone to epiallelic variation, which provides a reversible mechanism to escape avirulence effector recognition (71,72,94). Second, in hemibiotrophic pathogens that require living host tissue during colonization, effectors needed for the transition to the necrotrophic infection stage might induce early necrosis if they are expressed prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…Tight regulation of these avirulence effectors could limit the negative effects of the host immune responses, which may be especially relevant for avirulence factors such as Avr3D1 that induce only partial resistance (51). The location of effector genes in heterochromatic regions might also make them more prone to epiallelic variation, which provides a reversible mechanism to escape avirulence effector recognition (71,72,94). Second, in hemibiotrophic pathogens that require living host tissue during colonization, effectors needed for the transition to the necrotrophic infection stage might induce early necrosis if they are expressed prematurely.…”
Section: Discussionmentioning
confidence: 99%
“…Among these histone modifications, histone methylation/demethylation and acetylation/ deacetylation have been widely studied, which regulates many biological processes in plants, including development and responses to biotic and abiotic stresses [62,63]. The majority of histone methylation takes place on the lysine residue of histone H3, such as H3K4me3, H3K36me3, H3K79me3, H3K9me2 and H3K27me3, in which H3K4me3 and H3K27me3 are highly conserved epigenetic marks for gene activation and repression, respectively [64][65][66]. Histone methylation is dynamically regulated by the histone methyltransferases (HMTs) and histone demethylases (HDMs) [64][65][66].…”
Section: Histone Modificationmentioning
confidence: 99%
“…The majority of histone methylation takes place on the lysine residue of histone H3, such as H3K4me3, H3K36me3, H3K79me3, H3K9me2 and H3K27me3, in which H3K4me3 and H3K27me3 are highly conserved epigenetic marks for gene activation and repression, respectively [64][65][66]. Histone methylation is dynamically regulated by the histone methyltransferases (HMTs) and histone demethylases (HDMs) [64][65][66]. For instance, the repressive H3K27me3 modification is mediated by HMT complexes PRC1 and PRC2 recruited by various DNA-binding proteins.…”
Section: Histone Modificationmentioning
confidence: 99%
“…The majority of histone methylation takes place on the lysine residue of histone H3 in which H3K4 and H3K9 are highly conserved epigenetic markers for gene activation [ 34 , 35 ]. Histone methylation is dynamically regulated by histone methyltransferases ( HMTs ) and histone demethylases ( HDMs ) [ 31 , 36 ]. In this study, we reported for the first time the potential mechanism of bioactive compound biosynthesis regulated by H3K4 and H3K9 methylation in L. japonica , and elucidated the correlation among transcriptional levels of HMTs and HDTs , histone methylation levels, and bioactive compounds of L. japonica .…”
Section: Introductionmentioning
confidence: 99%